The impact of think pair share model on mathematics learning in elementary schools - Shila Majid Ardiyani; Gunarhadi Gunarhadi; Riyadi Riyadi (Intelektual Pustaka Media Utama, 2019)
One objective of mathematics learning is to solve problem and to communicate idea to get a solution. Human life is inseparable from social activity, including cooperation. Similarly, in mathematics learning sometimes students need friends to discuss with in solving mathematics problem. Cooperative learning model can be an alternative to bridge the difficulty the students encounter. The objective of research was to identify the impact of Think Pair Share type of Cooperative learning model on mathematics learning in elementary school. This study was a descriptive qualitative research. The subject of research was the fifth graders of three elementary schools in Karangpandan Sub District. Techniques of collecting data used were observation, interview, and documentation. Observation was conducted to observe the learning process using Think Pair Share-type of cooperative learning, interview to find out the impression and the impact the students experience, and documentation to find out the group’s work. The conclusion of research showed that there are some impacts found in mathematics learning using Think Pair Share type of cooperative learning related to: (1) group establishment; (2) learning environment; (3) learning achievement; (4) student participation; (5) information exchange; and (6) interpersonal relation.